2016
DOI: 10.1016/j.cmet.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte Ceramides Regulate Subcutaneous Adipose Browning, Inflammation, and Metabolism

Abstract: Adipocytes package incoming fatty acids into triglycerides and other glycerolipids, with only a fraction spilling into a parallel biosynthetic pathway that produces sphingolipids. Herein, we demonstrate that subcutaneous adipose tissue of type 2 diabetics contains considerably more sphingolipids than non-diabetic, BMI-matched counterparts. Whole-body and adipose tissue-specific inhibition/deletion of serine palmitoyltransferase (Sptlc), the first enzyme in the sphingolipid biosynthesis cascade, in mice markedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
208
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(245 citation statements)
references
References 37 publications
23
208
1
2
Order By: Relevance
“…However, the relative contribution of adiposity versus ceramides on insulin resistance was not addressed in this study. In other studies, ceramides were significantly elevated in SAT of obese diabetic as compared to obese nondiabetic individuals (42, 71) while ceramide content of VAT did not differ between these groups (71). More direct evidence of a role for ceramide in glucose homeostasis has been generated from several murine studies of altered ceramide metabolism (71, 150, 183, 384, 476, 522).…”
Section: Adiposity and Insulin Resistancementioning
confidence: 65%
See 1 more Smart Citation
“…However, the relative contribution of adiposity versus ceramides on insulin resistance was not addressed in this study. In other studies, ceramides were significantly elevated in SAT of obese diabetic as compared to obese nondiabetic individuals (42, 71) while ceramide content of VAT did not differ between these groups (71). More direct evidence of a role for ceramide in glucose homeostasis has been generated from several murine studies of altered ceramide metabolism (71, 150, 183, 384, 476, 522).…”
Section: Adiposity and Insulin Resistancementioning
confidence: 65%
“…More direct evidence of a role for ceramide in glucose homeostasis has been generated from several murine studies of altered ceramide metabolism (71, 150, 183, 384, 476, 522). Phenotypes of mice with reduced ceramide synthesis or increased ceramide catabolism are consistently characterized by improved glucose tolerance and insulin sensitivity (71, 150, 183, 476, 522). …”
Section: Adiposity and Insulin Resistancementioning
confidence: 99%
“…Ceramides activate the NLRP3 inflammasome. Whole body and adipocyte-specific depletion of ceramides in mice by inhibiting their synthesis by serine palmitoyltransferase induces adipose tissue browning and increases M2 macrophages 139 . Ablation of NLRP3 in mice improves insulin sensitivity, reduces IL-18, and reduces effector T cells in adipose tissue 140 .…”
Section: Macrophage and Adipocyte Dysfunction In Obese Adipose Tissuementioning
confidence: 99%
“…Another study demonstrated increased mitochondrial biogenesis and beta-oxidative capacity in brown adipocytes upon CerS6 deletion (31). Increased ETC activity has also been observed in adipocytes lacking serine palmitoyltransferase, an enzyme required for the synthesis of ceramide precursors (32). Although these experiments provide compelling evidence for a role for ceramides in modulating ETC activity, the mechanisms through which this occurs are unclear.…”
Section: Ceramide Mitochondrial Stress and Apoptosismentioning
confidence: 87%